Testing the pecking order theory of banks listed on the ghana stock exchange - SEY EUNICE (KNUST, 2024)
A thesis submitted to the institute of distance, kwame nkrumah university of science and technology, kumasi in partial fulfilment of the requirements for the award degree of master of science in accounting and finance